Electroencephalographic and psychomotor effects of chlorpromazine and risperidone relative to placebo in normal healthy volunteers - Hughes, A M (Blackwell Science Inc, 1999)
AIMS: To investigate the effects of single oral doses of chlorpromazine (50 mg) and risperidone (2 mg) relative to placebo on topographical electroencephalometry (CATEEM™) and psychomotor tests in 12 healthy male volunteers. METHODS: A double-blind, placebo-controlled, three-way crossover design using a double dummy blinding technique was utilized. Chlorpromazine was selected as representative of the ‘typical’ neuroleptics, being also highly sedative. Risperidone has been suggested as representative of the newer ‘atypical’ neuroleptics and is claimed to be only minimally sedative. Volunteers were dosed on 3 separate days with a minimum of 7 days interval between trial days. On each trial day volunteers were dosed twice. Dose 1 consisting of either chlorpromazine 50 mg or placebo to chlorpromazine, and dose 2 either risperidone 2 mg or placebo to risperidone. The volunteers were randomized so that each received either chlorpromazine or risperidone (or neither), but not both on an individual trial day. A 17 electrode quantitative topographical electroencephalograph (EEG) recording was taken for each volunteer before and after each dosing period. Seven psychomotor function tests were used to determine the effects of each treatment on psychomotor performance. RESULTS: The data confirm the cited reports of sedation following single oral doses of chlorpromazine 50 mg. However, 7 of the 12 volunteers dosed with risperidone 2 mg also reported drowsiness/lethargy which was of greater severity and duration than 5 of the 12 volunteers who reported somnolence following dosing with chlorpromazine 50 mg. Objective assessment of psychomotor impairment using a short battery of psychomotor function tests mirrored the subjective reports of somnolence in that the impairment in volunteers dosed with risperidone 2 mg was greater in extent and magnitude than in volunteers dosed with chlorpromazine 50 mg. With respect to the cortical quantitative electroencephalogram, both chlorpromazine (50 mg) and risperidone (2 mg) increased power (4.75–6.75 Hz) in keeping with cited effects of other neuroleptics on the quantitative EEG. In addition, there was a statistically significant increase (P<0.05) in α(1)(7.0–9.5 Hz) and β(1) (12.75–18.5 Hz) wavebands in volunteers dosed with risperidone 2 mg. Furthermore, based on estimates of variability, we propose that a 3 min eyes open and 3 min eyes closed quantitative EEG recording is sufficient to maintain adequate power for this technique, whilst allowing its application to early volunteer trials of novel neuroleptic agents. CONCLUSIONS: This study demonstrates that quantitative EEG can be utilized in the profiling of neuroleptic agents, and could be readily applied to the early profiling of novel neuroleptics in limited numbers of volunteers, early in drug development. The chosen battery of psychomotor tests has clearly demonstrable sensitivity to the quantification of the subjective reports of somnolence secondary to both chlorpromazine and risperidone.